2017
DOI: 10.1016/j.actbio.2017.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting for vascular and vascularized tissue biofabrication

Abstract: Biofabrication of living tissues and organs at the clinically-relevant volumes vitally depends on the integration of vascular network. Despite the great progress in traditional biofabrication approaches, building perfusable hierarchical vascular network is a major challenge. Bioprinting is an emerging technology to fabricate design-specific tissue constructs due to its ability to create complex, heterocellular structures with anatomical precision, which holds a great promise in fabrication of vascular or vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
306
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(310 citation statements)
references
References 192 publications
(263 reference statements)
0
306
0
4
Order By: Relevance
“…Based upon the mechanism of deposition, bioprinting can be defined in three broad categories-extrusion-based bioprinting (EBB), droplet-based bioprinting (DBB), and laser-based bioprinting (LBB)-the detailed mechanisms of which are available at several sources [55,56] . [57][58][59][60][61] . Thus, bio printing has attracted the attention of researchers working with the quest to devise improved solutions for osteochondral healing.…”
Section: Bioprinting For Osteochondral Engineer Ingmentioning
confidence: 99%
“…Based upon the mechanism of deposition, bioprinting can be defined in three broad categories-extrusion-based bioprinting (EBB), droplet-based bioprinting (DBB), and laser-based bioprinting (LBB)-the detailed mechanisms of which are available at several sources [55,56] . [57][58][59][60][61] . Thus, bio printing has attracted the attention of researchers working with the quest to devise improved solutions for osteochondral healing.…”
Section: Bioprinting For Osteochondral Engineer Ingmentioning
confidence: 99%
“…While several studies found that genetic factors such as mutations in candidate genes (high and low susceptibility) and copy number variations (CNV) [36] might impact risk for ASD, these factors are responsible for only 2–3% of ASD cases [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…We identified that synaptic proteins were significantly up- and down-regulated in fish brains (Table 1). The protein products of these genes are known to play a key role in synaptogenesis, and are also found to be associated with ASD [3, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…However, one of the biggest challenges of whole-organ engineering is that to create clinically relevant tissue, it needs to be vascularised [53]. Therefore, it is not remarkable that using bioprinting to create blood vessels, or vascularised tissue is a hot topic of research [54].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%